Recent developments in CrystFEL. Issue 2 (1st April 2016) - White, Thomas A.; Mariani, Valerio; Brehm, Wolfgang; Yefanov, Oleksandr; Barty, Anton; Beyerlein, Kenneth R.; Chervinskii, Fedor; Galli, Lorenzo; Gati, Cornelius; Nakane, Takanori; Tolstikova, Alexandra; Yamashita, Keitaro; et al.
Abstract : Developments in the CrystFEL software suite, for processing diffraction data from `serial crystallography' experiments, are described. Abstract : CrystFEL is a suite of programs for processing data from `serial crystallography' experiments, which are usually performed using X‐ray free‐electron lasers (FELs) but also increasingly with other X‐ray sources. The CrystFEL software suite has been under development since 2009, just before the first hard FEL experiments were performed, and has been significantly updated and improved since then. This article describes the most important improvements which have been made to CrystFEL since the first release version. These changes include the addition of new programs to the suite, the ability to resolve `indexing ambiguities' and several ways to improve the quality of the integrated data by more accurately modelling the underlying diffraction physics.